A (21150, 19050) GC-LDPC Decoder for NAND Flash Applications - Liao, Yen-Chin; Lin, Chien; Chang, Hsie-Chia; Lin, Shu (IEEE transactions on circuits and systems. I, Regular papers, 2019)
In this paper, a (21150, 19050) globally-coupled low-density parity check (GC-LDPC) code designed for NAND flash memories is presented. The proposed LDPC code comprises three disjoint subcodes which can be decoded independently. This highly structural parity check matrix contributes to efficient decoder implementation and flexible decoding flow control. Moreover, a two-phase local/global decoding procedure optimized for the proposed GC-LDPC code is introduced. Scenarios of collaborative decoding that leverages the special code structures are discussed. In the proposed decoder architecture, the pipelined processing elements with scheduling are employed to reduce the critical path and decoding latency as well. Implemented in UMC 65 nm process, the post-layout simulation shows a maximum decoding throughput of 4.32 Gb/s with the chip area 3.376 mm 2 .